2017
DOI: 10.1039/c7ra00570a
|View full text |Cite
|
Sign up to set email alerts
|

Comparatively studying the local atomic structures of metallic glasses upon cyclic-loading by computer simulations

Abstract: Through a variety of local structural analysis methods, it is revealed that the NixZr100–xMGs exhibit a combination of the icosahedral-, fcc- and hcp-like configurations, while the icosahedra or distorted icosahedra cover a dominant fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It is well realized by now that metallic glasses relax to lower energy states during the aging process and become more brittle, while rejuvenation and improved plasticity can be achieved using a number of experimental techniques, such as shot peening [4], cold rolling [5], high pressure torsion [6], ion irradiation [7], and cryogenic thermal cycling [8,9]. In turn, recent atomistic simulations have shown that periodically loaded disordered materials evolve towards lower energy states at sufficiently small strain amplitudes, whereas the yielding transition and shear localization occur at large amplitudes after a number of transient cycles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In addition, it was found that amorphous materials subjected to multiple thermal cycles might either relax or rejuvenate depending on the thermal amplitude, number of cycles, and processing history [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It is well realized by now that metallic glasses relax to lower energy states during the aging process and become more brittle, while rejuvenation and improved plasticity can be achieved using a number of experimental techniques, such as shot peening [4], cold rolling [5], high pressure torsion [6], ion irradiation [7], and cryogenic thermal cycling [8,9]. In turn, recent atomistic simulations have shown that periodically loaded disordered materials evolve towards lower energy states at sufficiently small strain amplitudes, whereas the yielding transition and shear localization occur at large amplitudes after a number of transient cycles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In addition, it was found that amorphous materials subjected to multiple thermal cycles might either relax or rejuvenate depending on the thermal amplitude, number of cycles, and processing history [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…respectively. We note that in a previous study 21 As seen in Z11 motif, the chemical order of four-fold symmetry varies significantly from that of five-fold symmetry. In this light, chemical order and structure are mutually interacted with each other.…”
Section: Structural and Chemical Ordermentioning
confidence: 42%
“…So far studies of the atomistic structures of undercooled liquid and glass of Ni-Zr system at the composition of 50 at% Zr are still very limited. Yang et al 21 22 developed an accurate semi-empirical embedded-atom method (EAM) potential of the Finnis-Sinclair (FS) type 23 to study the solid-liquid interface in the Ni50Zr50 alloy. The accuracy and efficiency of this EAM potential provides us with a reliable tool to perform extensive MD simulation to investigate the microscopic structural and chemical orders in the deeply undercooled and glassy Ni50Zr50 systems.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the fractions of the ten most populous types of polyhedra with the Voronoi index n 3 , n 4 , n 5 , n 6 at T = 300 K, 200 K, and 80 K. The 0, 1, 10, 2 type of polyhedron is the most populous at all three temperatures, although its fraction at T = 300 K is not much different from that of other polyhedra. It is an icosahedral-like cluster and is frequently observed in metallic glasses [22,[27][28][29][30][31][32][33]. The full icosahedron 0, 0, 12, 0 was also observed; however, the fraction was smaller than that of 0, 1, 10, 2 .…”
Section: Resultsmentioning
confidence: 89%